Preparation of a New Dosage Form of Metoclopramide Hydrochloride as Orodispersible Tablet - H. Tizkam, Hussam; A. Abdul Rassol, Alaa; A. Hussain, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2017)
Metoclopramide HCl (MTB) is a potent antiemetic drug used for the treatment of nausea and vomiting. Many trials were made to prepare a satisfactory MTB orodispersible tablet using direct compression method.Various super disintegrants were used in this study which are croscarmellose sodium (CCS), sodium starch glycolate (SSG) and crospovidone (CP). The latter was the best in terms of showing the fastest disintegration time in the mouth.Among the different diluents utilized, it was found that a combination of microcrystalline cellulose PH101 (MCC 101), mannitol, dicalcium phosphate dihydrate (DPD) and Glycine was the best in preparing MTB orodispersible tablet with fastest disintegration time in the mouth.The physical parameters of the prepared MTB orodispersible tablet were satisfactory as hardness (4 Kg), friability (0.5%) and mouth disintegration (23 sec).The overall results suggest that the prepared formula of MTB as orodispersible tablet could be utilized as a new dosage form for the oral administration. Key words: Orodispersible, metoclopramide, super disintegrant